Crime by the numbers: a criminologist's guide to R - Kaplan, Jacob (The R series, 2023)
"This book introduces the programming language R and covers the necessary skills to conduct quantitative research in criminology. While it can apply to other social science research, it does focus on skills specifically for criminology such as spatial joins, mapping, and scraping data from PDFs. The goal of this book is that by the end, a person without any prior programming experience can take raw crime data (e.g. from a .rds file, an Excel file, a PDF, from a website), be able to clean it, visualize the data, present it using R Markdown, and change it to a format ready for analysis (e.g. subset and aggregate the data)"--